Characterization of microsatellite loci in the dwarf eelgrass Zostera noltii (Zosteraceae) and cross-reactivity with Z. japonica - Coyer, J. A. (2014)
Zostera noltii is an important species of eelgrass occurring along European, north African, Mediterranean, Black Sea and Azov Sea coasts. Nine microsatellite loci were developed and no linkage disequilibrium was observed. Cross-amplification was observed for all loci (polymorphic) in Z. japonica ; only four loci amplified (monomorphic) in Z. marina.